2005
DOI: 10.1111/j.1551-2916.2005.00739.x
|View full text |Cite
|
Sign up to set email alerts
|

Pressureless Sintering of Zirconium Diboride

Abstract: Zirconium diboride (ZrB 2 ) ceramics were sintered to a relative density of B98% without applied external pressure. Densification studies were performed in the temperature range of 19001-21501C. Examination of bulk density as a function of temperature revealed that shrinkage started at B21001C, with significant densification occurring at only 21501C. At 21501C, isothermal holds were used to determine the effect of time on relative density and microstructure. For a hold time of 540 min at 21501C, ZrB 2 pellets … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
226
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 291 publications
(252 citation statements)
references
References 21 publications
11
226
2
Order By: Relevance
“…Within the detection limit of the XRD technique, it can be concluded that ZrO 2 and WC phases in the 40 vol.% WC composite are chemically stable when PECS was for 20 min even at 1850°C. The present observation is consistent with the work of Chamberlain et al reporting the direct reaction of ZrO 2 and WC to be thermodynamically favorable only above 1960°C [12]. However, it is in contradiction with other literature reports, revealing the presence of ZrC, W 2 C and even W phases as reaction products in ZrO 2 -WC composites during pressureless sintering in vacuum for 1 h at ≥1750°C [13] and the formation of ZrC when PECS of WC composites with 10 vol.% ZrO 2 for 1.5-4 min at 1700°C and 1800°C [5].…”
Section: Constituent Phasessupporting
confidence: 96%
“…Within the detection limit of the XRD technique, it can be concluded that ZrO 2 and WC phases in the 40 vol.% WC composite are chemically stable when PECS was for 20 min even at 1850°C. The present observation is consistent with the work of Chamberlain et al reporting the direct reaction of ZrO 2 and WC to be thermodynamically favorable only above 1960°C [12]. However, it is in contradiction with other literature reports, revealing the presence of ZrC, W 2 C and even W phases as reaction products in ZrO 2 -WC composites during pressureless sintering in vacuum for 1 h at ≥1750°C [13] and the formation of ZrC when PECS of WC composites with 10 vol.% ZrO 2 for 1.5-4 min at 1700°C and 1800°C [5].…”
Section: Constituent Phasessupporting
confidence: 96%
“…It is generally believed that the oxides of B 2 O 3 and ZrO 2 on the surface of B 4 C and Zr inhibit the densification by promoting coarsening through evaporation condensation at temperatures of 1500°C to 1800°C. [22][23][24] In the present case, it is proposed that any excess carbon in the B 4 C would reduce the B 2 O 3 or ZrO 2 (from oxidation of Zr or from ZrO 2 milling media) by the following reactions: 2ZrO 2 + B 4 C + 3C fi 2ZrB 2 + 4CO (g) and ZrO 2 + B 2 O 3 (l) + 3C fi ZrB 2 + 3CO (g). Recently, it has also been shown that these reactions are thermodynamically favorable at 1000°C and 1044°C, respectively, during vacuum sintering.…”
Section: B Effect Of Nonstoichiometry On Reaction and Densification mentioning
confidence: 97%
“…[2] Sintering is conducted at temperatures higher than 1700 8C depending on the sintering techniques (pressure assisted or pressureless) and/or sintering aids used. [3][4][5][6][7][8] ZrB 2 sintered bodies are usually manufactured with relatively simple geometrical shapes because their brittleness and high hardness make difficult the mechanical machining. Moreover, the requested diamond machining is usually expensive.…”
mentioning
confidence: 99%